Linking social movements: how international networks can better support community action about forests - Wollenberg, Eva Karoline; Colchester, M.; Mbugua, G.; Griffiths, T. (Center for International Forestry Research, 2005)
International networks in community forestry face challenges in linking with local social movements. We examine four efforts of international networks to overcome these challenges and better link with local people in Peru, Brazil, India and Kenya. The examples demonstrate that the networks created effective links by making funds available for meetings and local data collection; providing international analyses that helped people understand their own situation better; sharing strategies for media, policy and letter campaigns; helping to disseminate information about local people’s priorities, providing independent assessments and building local people’s confidence. Efforts to improve communications technologies required a better understanding of local conditions. Networks will be more relevant to local movements to the extent that they are regularly active at the local level, can respond flexibly to local needs and small-scale events, and work with an array of national partners. The effectiveness of networks in carrying out these tasks may require a careful balance between linking to versus working at the local level.